A Novel Nanocomposite Scaffold Based on Polyurethane (PU) Containing Cobalt Nanoparticles (CoNPs) for Bone Tissue Engineering Applications - Norouz, Faezeh; Poormoghadam, Delaram; Halabian, Raheleh; Ghiasi, Mohsen; Monfaredi, Monireh; Salimi, Ali (Current Stem Cell Research & Therapy, 2023)
Background: Bone tissue engineering, as a relatively new approach, has focused on combining biodegradable scaffolds, cells, and biologically active molecules for the recovery of different damaged tissues, such as bone defects. Polyurethane (PU), as a synthetic polymer, benefits from a porous structure which impersonates bone's natural environment. However, PU lacks osteoinduction activities. Cobalt nanoparticles (CoNPs) stimulate angiogenesis and biomineralization, which greatly favors osteogenesis. Methods: Here, we designed a novel scaffold based on PU and combined it with CoNPs for bone regeneration applications. The composition and structure of PU-CoNPs nanocomposite were characterized using Fourier transform infrared spectroscopy (FTIR), scanning electron microscopy (SEM), and differential scanning calorimetry (DSC). MTT and AO data showed biocompatibility and enhanced viability and proliferation of fibroblasts on PU-CoNPs scaffold. Ascorbic acid-2-phosphate, β-glycerophosphate, and dexamethasone-induced osteogenesis for 14 days. Results: The alkaline phosphatase test asserts the increased mineralization of hADSCs cultured on PUCoNPs compared to pure PU scaffold. Further, the results disclosed an elevated osteogenic differentiation at the level of genes and proteins using immunocytochemical analysis (ICC) and quantitative real-time PCR (qPCR). Conclusion: These findings provide an evidence that PU-CoNPs nanocomposite might be a promising candidate for bone repair applications.
Keywords: tissue engineering